Efektivitas Pelaksanaan Fungsi Pengawasan Keimigrasian Terhadap Pelanggaran Izin Tinggal Overstay di Kantor Imigrasi Kelas 1 TPI Kupang - Tri Melani Gultom; Umbu Lily Pekuwali; Stefanus Kurniadi Janggur (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The high level of international mobility has influenced the influx of foreign nationals into Indonesia, particularly in East Nusa Tenggara Province, which has significant potential as a tourist destination and occupies a strategic position as a border region. This condition has the potential to give rise to various immigration violations, one of which is Overstay, namely the presence of foreign nationals who remain in Indonesia beyond the period permitted by their stay permits. This study aims to analyze the effectiveness of the implementation of immigration supervisory functions in addressing Overstay violations at the Class I Immigration Office with Immigration Checkpoint (TPI) Kupang and to identify the factors affecting its effectiveness. This study employs an empirical juridical method with a descriptive approach. Data were collected through interviews with immigration officers, field observations, and document studies. The collected data were analyzed qualitatively by relating statutory regulations to facts found in the field. The results indicate that the implementation of immigration supervision has been carried out in accordance with the applicable immigration laws and regulations, which include: (1) administrative supervision; (2) field operational supervision through intelligence operations, independent operations, cooperation with related agencies, and community participation; and (3) the imposition of sanctions on violators. However, the implementation of immigration supervision has not been fully effective, as Overstay violations are still found within the jurisdiction of the Class I Immigration Office with Immigration Checkpoint (TPI) Kupang. Factors influencing the effectiveness of immigration supervision include legal factors, law enforcement officers, facilities and infrastructure, and community culture.